Design optimization and manufacturing of an innovative precise low-intensity magnetic separator based on a multiphysics model. (1st September 2021) - Wang, Feiwang; Tang, Dongdong; Dai, Huixin; Zhang, Shitao; Gao, Likun; Gong, Minghui
Highlights: An innovative precise low-intensity magnetic separator (PLIMS) was designed and manufactured. The design parameters of the magnet assembly and operational parameters of PLIMS were optimized. The remnant flux density of the magnet assembly was designed to gradually increase from low to high. The principle of PLIMS was explained by simulating the dynamic capture process of the magnetic particles. Abstract: A wet low-intensity magnetic separator (LIMS) is the workhorse for winning magnetite from a slurry. However, the issue with optimizing LIMS is the balance between attracting too much material and obtaining mixed grains of extremely low-grade material (less than 20 vol% magnetite) in the concentrates and attracting too little material and losing the fine liberated magnetite to the tailings. In this study, an innovative precise low-intensity magnetic separator (PLIMS) was designed and optimized based on a multiphysics numerical model. The design parameters of the magnetic assembly and operational parameters were designed and optimized by predicting the separation performance and particle dynamic trajectory of the PLIMS. In particular, the remnant flux density of the magnet assembly was designed to gradually increase from low to high along the flow direction of the slurry, so that the magnetic particles were subjected to precise magnetic force during the separation process. When the magnetic force is greater than the competitive forces, the magnetic particles are captured on the surface of the drum. Then, the captured particles with different liberation degrees and particle sizes are taken out of the separation zone via rotating drum one by one and become concentrated products of multiple grades. The aim of the process is to capture the high liberation magnetite into the main concentrates to obtain high-grade concentrate products, while also capture the low-grade intergrowth particles into the minor concentrates as much as possible to obtain higher recovery. Furthermore, this principle of magnetic separation of PLIMS was explained by simulating the dynamic capture process of the magnetic particles. To verify whether the design concept of gradient magnet assembly (GMA) has advantages, another uniform magnet assembly (UMA) with the same remnant flux density of all permanent magnets was designed. Comparative studies of the magnetic field distribution and magnetic separation performance of GMA and UMA show that PLIMS of the GMA has more significant separation performance. Finally, a laboratory-level PLIMS with a drum diameter of 300 mm ( ϕ 300-PLIMS) was manufactured based on all the optimization studies above. By comparing the experimental results with simulated results, the accuracy of the PLIMS recovery and grade prediction results were verified.